2011
DOI: 10.1007/s00439-011-1000-2
|View full text |Cite
|
Sign up to set email alerts
|

ATXN-2 CAG repeat expansions are interrupted in ALS patients

Abstract: It has recently been suggested that short expansions of CAG repeat in the gene ATXN-2 causing SCA2 (spinocerebellar ataxia type 2) are associated with an increased risk of amyotrophic lateral sclerosis (ALS) in the populations of the USA and northern Europe. In this study, we investigated the role of ATXN-2 in Italian patients clinically diagnosed with ALS and characterized the molecular structure of ATXN-2 expansions. We assessed the size of the CAG repeat in ATXN-2 exon 1 in 232 Italian ALS patients and 395 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 20 publications
3
46
0
1
Order By: Relevance
“…20 Because of the presence of TDP-43 inclusions in many neurodegenerative diseases and the heterogeneity of their clinical presentation, a number of studies have evaluated ATXN2 repeat sizes in patients with neurodegenerative diseases. 17,[21][22][23][24][25][26][27][28][29][30][31][32][33] All the studies confirmed a significant association between intermediary repeat lengths and ALS, which is even stronger when familial cases are considered separately from sporadic cases. An association has also been found with PSP.…”
Section: Figurementioning
confidence: 70%
“…20 Because of the presence of TDP-43 inclusions in many neurodegenerative diseases and the heterogeneity of their clinical presentation, a number of studies have evaluated ATXN2 repeat sizes in patients with neurodegenerative diseases. 17,[21][22][23][24][25][26][27][28][29][30][31][32][33] All the studies confirmed a significant association between intermediary repeat lengths and ALS, which is even stronger when familial cases are considered separately from sporadic cases. An association has also been found with PSP.…”
Section: Figurementioning
confidence: 70%
“…6,8,12 Normal ATXN-2 alleles were in fact #31 repeats in several studies. 5,6,8 In our sALS cohort from southern Italy, we found a significant association with ATXN-2 when PolyQ repeats were $28 (2.7% alleles), with only 0.5% expanded alleles in controls. This makes our finding closer to the study of the American and Chinese ALS cohorts, where the disease was shown to be associated with ATXN-2 repeat expansions 27-33 and $27, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…[5][6][7][8][9][10][11][12] The finding that ATXN-1 PolyQ repeats $32 also represent a risk factor for ALS is novel, and suggests that intermediate expansions of both ataxins might indeed be involved in the pathogenesis of this neurodegenerative disorder.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maya modelinde, SCA2 ile ilişkilendirilmiş ataksin-2 proteininin ortologu olan Pbp1'in, TDP-43 aşırı üretimine bağlı toksisiteyi düzenlediğinin görülmesi üzerine ALS hastalarında yapılan çalışmalar, ataksin-2'nin ALS oluşumu için bugüne kadar bulunmuş en önemli risk faktörü olduğunu göstermiştir. Ataksin-2 ve TDP-43'ün etkileşim mekanizması henüz netlik kazanmamıştır (74)(75)(76)(77)(78)(79)(80)(81).…”
Section: Tdp-43 Ve Model Sistemlerunclassified